Transactions on Computational Collective Intelligence VII - Nguyen, Ngoc Thanh; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
These Transactions publish research in computer-based methods of computational collective intelligence (CCI) and their applications in a wide range of fields such as the Semantic Web, social networks and multiagent systems. TCCI strives to cover new methodological, theoretical and practical aspects of CCI understood as the form of intelligence that emerges from the collaboration and competition of many individuals (artificial and/or natural). The application of multiple computational intelligence technologies such as fuzzy systems, evolutionary computation, neural systems, consensus theory, etc., aims to support human and other collective intelligence and to create new forms of CCI in natural and/or artificial systems. This seventh issue contains a collection of ten carefully selected and thorougly revised contributions.
Keywords: Computer science; Software engineering; Information storage and retrieval systems; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; User Interfaces and Human Computer Interaction; Software Engineering; e-Commerce/e-business.